Development of intellektual potential students in the development of higher education (Multidisciplinary Journal of Science and Technology, 2024)
In the article in higher education In higher education, the Annotal Teacher's importance is important in the  course of today's education, modernization processes, globalization processes for innovative society, training  specialists, training, training systems, pedagogical activity, to modernize the efficiency of pedagogical  activities